Vasoplegic versus septic shock in cardiac surgery. Possibilities of differentiating between them and implementing appropriate therapy - Kudliński, Bartosz; Marczak, Jakub; Cichoń, Romuald (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Among patients undergoing on-pump cardiac surgery (cardiopulmonary bypass – CPB), there is a population of patients who, shortly after the end of the procedure (and CPB), exhibit symptoms of generalized hypotension related to very low systemic vascular resistance, the treatment of which requires very large doses of vasoconstrictors. This clinical condition is known as vasodilatation or vasoplegic shock (a distributive shock). Risk factors of postoperative vasoplegia such as initial patient condition, preoperative pharmacotherapy, cardiac procedure type, extracorporeal perfusion, the activation of intrinsic mechanisms leading to vasodilatation, and infectious factors (complicating the previously “sterile” vasoplegia course) should be taken into consideration when planning the treatment and aiming to improve the postoperative outcome. Whether vasoplegia is of infectious or sterile etiology remains the big issue which dictates postoperative therapy: empirical antibiotic de-escalation therapy vs. standard perioperative antibiotic prophylaxis.